Improved oxygen reduction activity of porous carbon materials by self-doping nitrogen derived from PVP with urea as a promoter. (20th September 2015) - Zhang, Jian; Li, Qidong; Amiinu, Ibrahim Saana; Wu, Hui; Zhang, Chenyu; Cheng, Kun; Zhou, Huang; Mu, Shichun
Graphical abstract: Highlights: N-doped nano porous carbon is prepared by a simple but template–free method. Such N-doped carbon owns a porous structure with a high surface area. It possesses the same onset potential compared to the commercial Pt/C catalyst in alkaline media. It also exhibits impressive durability and excellent fuel resistance over Pt/C. Abstract: A novel nitrogen (N)-doped carbon catalyst has been prepared using a simple but effective method by pyrolyzing polyvinylpyrrolidone (PVP) as the precursor and urea as a promoter. The physicochemical measurements results show that the sample upon adding urea not only has a porous structure with high surface area, but possesses more active N content and edge defects than the sample without adding urea. The electrochemical characterizations show that the catalyst owns a good oxygen reduction reaction (ORR) activity and a nearly 4-electron pathway selectivity in alkaline media. Notably, the onset potential of the catalyst is equal to the commercial Pt/C catalyst, and its half-wave potential is only 30 mV lower than that of Pt/C. Moreover, our catalyst exhibits impressive durability and excellent resistance to methanol crossover and CO poisoning in comparison with Pt/C catalyst.